Crossing the threshold of divine revelation - Abraham, William J. (William James), 1947- (Grand Rapids, Mich. : William B. Eerdmans Pub., 2006)
The last few decades have seen a revolution in debates about the rationality of Christian belief. Among the array of current options for justifying religious belief, however, nearly every one assumes that a general theory of knowing and a minimal version of theism must be adopted before the rationality of Christian belief can be tackled. William J. Abraham confronts both of these assumptions, arguing that epistemology must begin with its particular target of inquiry in Abrahams case the full-blooded 2canonical theism3 of the early, undivided Christian Church. He argues, moreover, that special divine revelation forms a crucial threshold at the entrance to the epistemology of Christian Belief. Sure to intrigue philosophers, theologians, and curious students, Abrahams robust vision of Christian faith provides a creative solution to any of the current difficulties in philosophy and theology.
Reorientation -- Epistemic platitudes and theology -- Canonical theism and proper epistemic fit -- Revelation, the oculis contemplationis, and evidence -- Crossing the threshold of divine revelation -- Divine revelation and canonical doctrine -- Conversion -- Unbelief, belief, and loss of faith -- Defeaters and objections -- Revelation and language -- Rationality, justification, and knowledge.
Includes bibliographical references and index.
Keywords: Christianity -- Philosophy; Philosophical theology; Revelation